PENGEMBANGAN SISTEM INFORMASI AKUNTANSI KOPERASI (SIKOP) BERBASIS SAK ETAP DAN PERMEN KUKM DI KOPERASI “KRASAN” SURABAYA - Salman, Kautsar Riza; Shonhadji, Nanang; Djunaedi, Arif Zeinfiki; Mei Murni, Nur Suci I.; Kurniawati, Sri Lestari; Al Hafidz, Mohammad; Kholid, Ikhwan; Suparno, Suparno (Jurnal Terapan Abdimas, 2023)
Abstract.  The KPRI Krasan Cooperative was established 40 years ago and has experienced growth in terms of the number of members and the savings it manages. Based on the results of observations and discussion forums with cooperative management, information was obtained that the bookkeeping carried out by cooperatives was still manual and part of it used the Microsoft Excel program. One of the weaknesses of the current system is the emergence of difficulties in tracing data between cash accounts and bank accounts. This community service activity aims to develop a good administrative system and cooperative accounting information system (SIKOP) software that is tailored to the needs of partners. The implementation method that is carried out includes the focus group discussion stage with partners, the system development stage and the assistance stage in operating the system. The results obtained in community service activities in the form of cooperative accounting information system software (SIKOP) consist of input, process and output. The cooperative accounting information system was developed with reference to two main references, namely Financial Accounting Standards (SAK) for Entities Without Public Accountability (ETAP) and Regulations of the Minister of Cooperatives and Small and Medium Enterprises (Permen KUKM). In addition, the results of community service activities also provide assistance to partners starting from input transactions to producing financial reports. The resulting output is a complete cooperative financial report consisting of a statement of financial position, a statement of profit and loss and other comprehensive income, a statement of changes in equity, a statement of cash flows, and notes to financial statements.  Abstrak. Koperasi KPRI Krasan telah berdiri 40 tahun lalu dan telah mengalami pertumbuhan dari sisi jumlah anggota dan dana simpanan yang dikelolanya. Berdasarkan hasil pengamatan dan forum diskusi dengan pengurus koperasi, diperoleh informasi bahwa pembukuan yang dijalankan koperasi masih bersifat manual dan sebagiannya digunakan program Microsoft Excel.  Kelemahan dari sistem yang berjalan, salah satunya adalah timbulnya kesulitan dalam melakukan tracing data antara rekening kas dan rekening bank. Kegiatan pengabdian masyarakat ini bertujuan untuk mengembangkan sebuah sistem administrasi yang baik dan software sistem informasi akuntansi koperasi (SIKOP) yang disesuaikan dengan kebutuhan mitra. Metode pelaksanaan yang dijalankan meliputi tahap focus group discussion dengan mitra, tahap pengembangan sistem dan tahap pendampingan dalam mengoperasikan sistem. Hasil yang diperoleh dalam kegiatan pengabdian masyarakat berupa software sistem informasi akuntansi koperasi (SIKOP) terdiri dari input, proses, dan output. Sistem informasi akuntansi koperasi dikembangkan dengan mengacu pada dua rujukan utama yaitu Standar Akuntansi Keuangan (SAK) Entitas Tanpa Akuntabilitas Publik (ETAP) dan  Peraturan Menteri Koperasi dan Usaha Kecil dan Menengah (Permen KUKM). Selain itu, hasil kegiatan pengabdian juga melakukan pendampingan kepada mitra yang dimulai dari input transaksi sampai dengan dihasilkannya laporan keuangan. Output yang dihasilkan adalah laporan keuangan lengkap koperasi yang terdiri dari laporan posisi keuangan, laporan laba rugi dan penghasilan komprehensif lain, laporan perubahan ekuitas, laporan arus kas, dan catatan atas laporan keuangan.